2021
DOI: 10.3390/ma14041001
|View full text |Cite
|
Sign up to set email alerts
|

Very-High-Cycle Fatigue Behavior of Inconel 718 Alloy Fabricated by Selective Laser Melting at Elevated Temperature

Abstract: This study investigates the very-high-cycle fatigue (VHCF) behavior at elevated temperature (650 °C) of the Inconel 718 alloy fabricated by selective laser melting (SLM). The results are compared with those of the wrought alloy. Large columnar grain with a cellular structure in the grain interior and Laves/δ phases precipitated along the grain boundaries were exhibited in the SLM alloy, while fine equiaxed grains were present in the wrought alloy. The elevated temperature had a minor effect on the fatigue resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The obtained fatigue life values were compared with the results of the fatigue test at an ambient temperature of about 22 °C ± 5°C, but the loading frequency, in this case, was f = 20,000 kHz. Fatigue failure and fatigue life are affected by several factors such as the formation of oxides, which form at high temperatures at the surface and affect the mechanism of fatigue crack closure by excluding phases such as BCT DO 22 Ni 3 Nb γ″-phase and orthorhombic D0 a Ni 3 Nb δ-phase, as demonstrated in Ling et al [ 64 ]; the frequency of loading and the number of cycles to fracture, as reported by Song et al [ 32 ]; or the heat treatment method, as reported by Zhao et al [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The obtained fatigue life values were compared with the results of the fatigue test at an ambient temperature of about 22 °C ± 5°C, but the loading frequency, in this case, was f = 20,000 kHz. Fatigue failure and fatigue life are affected by several factors such as the formation of oxides, which form at high temperatures at the surface and affect the mechanism of fatigue crack closure by excluding phases such as BCT DO 22 Ni 3 Nb γ″-phase and orthorhombic D0 a Ni 3 Nb δ-phase, as demonstrated in Ling et al [ 64 ]; the frequency of loading and the number of cycles to fracture, as reported by Song et al [ 32 ]; or the heat treatment method, as reported by Zhao et al [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This load method is more complex and combines bending and tensile load, which corresponds to significantly lower values of fatigue life compared to the classic push–pull load. The obtained results are unique in that most authors [ 32 , 64 , 65 ] have performed fatigue tests either only at ambient temperature and with a low load frequency or with a different parameter of the cycle asymmetry R. The data on increased δ-phase volume fraction and its influence on fatigue life have not been studied up until now. For this reason, we considered the results of high-temperature fatigue and its comparison with the fatigue life obtained at ambient temperature to be unique, especially if they were made on materials with the same grain size and the same processing method (i.e., the effect of changing the grain size), so a different γ′/γ″ phase ratio was eliminated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The visual analysis of the fracture surface (fractography) shows for the six tests presented in Figures 6-8 a smooth and a rough surface, which are separated by red lines as a guide for the eye. Cracks are generated and grow slowly in the smooth surface area [33], before fast crack growth occurs when the remaining cross-section area can no longer withstand the applied deformation. Therefore, it can be concluded that crack growth occurs, which can be followed in the mechanical stress response by the I 2/1 intensity.…”
Section: Crack Detectionmentioning
confidence: 99%